2005
DOI: 10.1007/s00018-005-5478-4
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil factors

Abstract: There is convincing evidence that trefoil factors (TFFs) do play an important role in tumourigenesis. However, their specific roles in cancer are not yet clear. Recently, TFFs have been shown to interfere with crucial biological processes such as cell proliferation, differentiation, apoptosis and angiogenesis. Research on the function of TFFs and its relationship with specific signal transduction pathways has also advanced significantly. As a consequence, some ideas about the role of TFFs in cancer have starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Of interest was the dramatic up-regulation of another ER-regulated gene, TFF1 [33], trefoil factor 1 (Fig. 2C), which is normally expressed in the epithelium of the breast and ovary [34], [35]. It is also expressed in gastric mucosal cells, where its function is to stabilize the mucosal layer and protect tissue from cellular injury [36].…”
Section: Resultsmentioning
confidence: 99%
“…Of interest was the dramatic up-regulation of another ER-regulated gene, TFF1 [33], trefoil factor 1 (Fig. 2C), which is normally expressed in the epithelium of the breast and ovary [34], [35]. It is also expressed in gastric mucosal cells, where its function is to stabilize the mucosal layer and protect tissue from cellular injury [36].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, TFF1 messenger RNA and/or protein have been shown to be focally expressed by normal mammary ducts (Poulsom et al , 1997; Wilson et al , 2006; Madsen et al , 2007; Vestergaard et al , 2008), and TFF1 is a human milk component (Vestergaard et al , 2008). However, in breast cancers, as in various other cancers, TFF1 expression is not downregulated as observed in gastric tumors, but strongly induced (Ribieras et al , 1998; Regalo et al , 2005), suggesting a possible function as an oncogene (Perry et al , 2008). …”
Section: Discussionmentioning
confidence: 87%
“…Indeed, TFF1 promotes epithelial restitution after injury and protects the integrity of the epithelial barrier (Hoffmann, 2005). Moreover, TFF1 is also expressed, but to a lesser extent, by normal epithelial cells of numerous organs (eyes, lung, ovary and salivary gland) (Regalo et al , 2005; Madsen et al , 2007; Buron et al , 2008). To date, the TFF1 function during malignant processes is not clearly defined, as epithelial cell transformation might lead to downregulation of TFF1 expression (that is, in the stomach) or to the induction of TFF1 expression (that is, in various organs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the higher levels of TFF3 levels in the serum of lung cancer patients may also be attributed to the histological changes in other tissues, especially for patients with late stages of lung cancers, since TFF1 is mainly expressed in the stomach and colon; TFF2 is mainly localized in the stomach; TFF3 is principally expressed in the intestines (22,53). We analyzed the correlation between the levels of serum TFF3 and the stages of the investigated 130 lung cancer patients using the statistical software.…”
Section: Discussionmentioning
confidence: 99%
“…Although TFFs have been involved in the protection of the gastrointestinal tract against mucosal damage (11), their oncogenic potential has been extensively reported, including their roles in cell proliferation (1215), apoptosis (1214,16,17), migration and invasion (14,16,18,19) and angiogenesis (20,21). TFF proteins levels have been found to be related to the development of breast cancer (2233), gastric cancer (21,22,3438), colon cancer (39,40), and prostate cancer (41–43). It has also been reported that TFF proteins are related to lung cancers (23,4448).…”
Section: Introductionmentioning
confidence: 99%